Seguindo Maria: turismo cultural - religioso para Santa Maria e região/RS - Coelho, Eva Regina Barbosa (2011)
The city of Santa Maria, RS state, is well-known as a religious center of Marian devotion and is an attraction for pilgrims and visitors, mainly because of the annual pilgrimage of Our Lady Medianeira . Silveira Martins, also in the central region of RS state, emerged linked to Santa Maria as host city of the fourth region of the Italian immigration in 1877. This town maintains a strong devotion for Mother Mary once this image was brought from Italian immigrants. This relation and the characteristics of the popular devotion is what motivated this paper. Its main purpose is to collect data which will allow us to build a religious and cultural itinerary, involving pilgrimage places and devotion to Mother Mary in the central region of RS state, Brazil. As a geographical cut, it was established that the region between Santa Maria and Silveira Martins would be the principal focus of this paper because of all the reasons mentioned above and because of the places selected, as the Sanctuaries and festivities that compose this itinerary, which follows: Diocesan Cathedral, Basilica of Our Lady Medianeira , Sanctuary of Schoenstatt, Church of Our Lady Dores , in Santa Maria; Sanctuary of Our lady of Health and Sanctuary of Our Lady of Pompeii, in Silveira Martins. Methodologically, an exploratory research was used, employing a historical method of procedure, from the technique of bibliographical investigation, of observation and of the qualitative appreciation of the collected information. The conceptual categories discussed told about Cultural Estate, Tourism, and the Catholic Identity of Rio Grande do Sul state, pilgrimage. The main findings are about the characterization of the religious identity of this region as a result of the propagation of the popular Catholicism, characterized by a devotional dimension mainly directed to the Marian cult, expressed currently in popular religious parties like pilgrimages, corteges and promises considered as inheritance of the Portuguese settlers, Indians missionaries, black people, people from Açores and Italian immigrants.